ASSESSMENT OF NECESSARY FINANCIAL EXPENSES ON THE DRUG SUPPLY OF THE PATIENTS WITH ORPHAN DISEASES IN THE RUSSIAN FEDERATION - M. V. Sura; K. V. Gerasimova; V. V. Omelyanovskiy; M. V. Avksentyeva (IRBIS LLC, 2015)
the article presents the results of cost calculation on the drug supply of the patients with orphan diseases, included in the list of orphan diseases (24 diseases) by the RF Government Regulation of April 26, 2012 № 403. Calculation was performed based on the data of registered patients with orphan diseases (OD) in 83 territorial entities of the Russian Federation in 2013 and based on the average-weighted costs of their drug therapy. Data on registered patients with OD was obtained because of the official request of the Expert Board on Healthcare of the Council of the Federation Committee on Social Policy that was sent to healthcare regulatory bodies of the 83 territorial entities of the Russian Federation. Average-weighted cost calculation of drug treatment (or of specialized nutrition care) of the patients with OD was carried out in accordance with medical care standards and expert assessment. As part of the analysis of the standards the search for pathogenic therapy medications was carried out, in the absence of which - there was a search for supportive care medications that critically affect survivability of the patients with OD. According to the selected list of drugs, information about duration, frequency of prescription, average daily and course dose, was analyzed. In the absence of medical care standards, and in order to verify some questions concerning drug therapy of patients with OD consultations with experts were held. Because of conducted calculation, total average-weighted costs of pharmacotherapy for 24 orphan diseases were 15.73 bln rubles per year (6.36 bln rubles for children and 9.37 bln rubles for adults) for 11 173 registered patients that by 3.3 exceeds current amount of finance. Pathogenetic pharmacotherapy of Mucopolysaccharidoses type VI and II proved to be the most expensive treatment per one patient per year: average-weighted costs per one child with Mucopolysaccharidoses type VI amounted to 40.90 mln rubles, per one adult - to 71.50 mln rubles; for Mucopolysaccharidoses type II costs were 29.60 and 51.83 mln rubles respectively. In order to increase effectiveness of the system of drug supply of the patients with OD and to optimize state expenses for this group of patients it is necessary to approve the entire range of financially balanced and science based medical care standards, to define the legal status of orphan drugs and to carry out state regulation of prices, to ensure increase of regional funding supported by involvement of federal budget funds, to define the list of orphan drugs, to implement state regulation measures to create incentives for pharmaceutical companies to reduce prices for orphan drugs.